Is telemedicine a holy grail in healthcare policy: clinicians’ and patients’ perspectives from an Apex Institution in Western India - Nainsi Gupta; Manoj Kumar Gupta; Nitin Kumar Joshi; Neha Mantri; G. Sridevi; Mamta Patel; Akhil Dhanesh Goel; Kuldeep Singh; M. K. Garg; Pankaj Bhardwaj (BMC Health Services Research, 2023)
Abstract Background This study aimed to explore the perception of doctors regarding telemedicine consultations and the level of patient satisfaction with the services received through teleconsultations. Methods This cross-sectional study was conducted on clinicians who provided teleconsultations and patients who received teleconsultations in an Apex healthcare institution in Western India. Semi-structured interview schedules were used to record the quantitative and qualitative information. Clinicians’ perceptions and patients’ satisfaction were assessed using two different 5-point Likert scales. Data were analyzed using SPSS v.23 using non-parametric tests (Kruskal Wallis and Mann-Whitney U). Results A total of 52 clinicians who delivered teleconsultations and 134 patients who received teleconsultations from those doctors were interviewed in this study. For 69% of doctors, telemedicine was feasible to implement, and for the rest, it was challenging. Doctors believe telemedicine is convenient for patients (77%) and prevents the transmission of infection (94.2%). Difficulty in clinical evaluation (73%), communication (55.7%), network connectivity (34%), diagnosis and investigations (32%), and patients’ e-illiteracy (32%) were the most common challenges faced by clinicians. Patients’ experiences were positive in terms of ease of registration (82.1%), audio quality (100%), freedom to discuss medicine (94.8%), and comprehension of the diagnoses (88.1%). Patients expressed satisfaction with the length of the teleconsultation (81.4%), the advice and care they received (78.4%), and the manner and communication of the clinicians (78.4%). Conclusions Though there were some challenges in the implementation of telemedicine, the clinicians perceived it quite helpful. The majority of the patients were satisfied with teleconsultation services. Difficulty in registration, lack of communication, and a deep-rooted mindset of physical consultations were the primary concerns from the patient side.